Efek Penempatan dan Kepuasan Kerja terhadap Produktivitas : Studi Kasus pada PT. Rezki Laifasto - Ramli, Nurleli (Jurnal Riset Bisnis dan Investasi, 2020)
This research aims to test the effect of employee’s work placement and satisfaction on the productivity in performing. It is case study conducted at PT. Reski Laifasto of Makassar Branch. The sample of this research consists of 71 employees. The result of this research discloses that work placement and satisfaction provide the positive effect on the productivity. This result indicates that the level of employee’s work productivity at PT. Reski Laifasto of Makassar Branch is determined by good work placement and the effect of satisfaction of work employee